Engagement of adolescents with ADHD in a narrative-centered game-based behavior change environment to reduce alcohol use - Pugatch, Marianne; Blum, Nathan J.; Barbaresi, William J.; Rowe, Jonathan; Berna, Mark; Hennigan, Sean; Giovanelli, Alison; Penilla, Carlos; Tebb, Kathleen P.; Mott, Megan; Kumaran, Vikram; Buckelew, Sara; et al. (Frontiers in Education, 2024)
Background: Attention deficit hyperactivity disorder (ADHD) affects about 13% of adolescents and is associated with substance use-related morbidity and mortality. While evidence on effective interventions to reduce alcohol use among adolescents with ADHD is limited, parent-teen communication about alcohol use has been found protective. Other approaches, such as educational interventions, hold promise to reduce alcohol-related harms in adolescents with ADHD. Digital technology offers an innovative approach to health behavior change, expanding access to services and may promote learning for neurodiverse youth, including teens with ADHD. INSPIRE, a narrative-centered game-based behavior change environment designed to promote self-regulation and self-efficacy to prevent risky alcohol use, has been found to engage a general adolescent population. The goals of this pilot study are 1) to examine the engagement of youth with ADHD in INSPIRE and 2) to examine if INSPIRE fosters parent-teen communication. Method: Adolescents diagnosed with ADHD aged 14-16 were recruited from developmental medicine clinics and invited to a focus group offered via Zoom. Participants completed a pre-survey, interacted with the INSPIRE game, and answered post-survey and open-ended questions about their gaming experience during the focus group. Engagement was measured through both self-report using subscales from the User Engagement Scale and computer data; survey and qualitative data collected information on parent-teen communication. Univariate statistics described adolescent characteristics, Rank-sum and Fisher’s exact tests examined relationships among variables, and qualitative analysis identified themes in open-ended questions. Results: Of adolescent participants (N=40), 45% identified as female, 17.5% Black, 7.5%, Hispanic, and 62.5% White. Post-survey mean engagement subscales of Usability (on a 5-point scale) was 3.67 (SD = .74), and Satisfaction was 3.63 (SD = .75). Computer data indicated that participants played the game for a median of 24 minutes. Adolescents shared that playing the game strengthened refusal skills and their ability to navigate social gatherings with alcohol. Post-survey, 63% planned to share information from INSPIRE with a parent. Conclusions: Findings suggest that INSPIRE may support facilitating youth with ADHD to learn the developmental competencies needed to mitigate risk and thrive. INSPIRE warrants further testing to explore its impact on alcohol use in youth with ADHD.